The multifunctional peptide DN‐9 produced peripherally acting antinociception in inflammatory and neuropathic pain via μ‐ and κ‐opioid receptors. (23rd December 2019) - Xu, Biao; Zhang, Mengna; Shi, Xuerui; Zhang, Run; Chen, Dan; Chen, Yong; Wang, Zilong; Qiu, Yu; Zhang, Ting; Xu, Kangtai; Zhang, Xiaoyu; Liedtke, Wolfgang; et al.
Abstract : Background and Purpose: Considerable effort has recently been directed at developing multifunctional opioid drugs to minimize the unwanted side effects of opioid analgesics. We have developed a novel multifunctional opioid agonist, DN‐9. Here, we studied the analgesic profiles and related side effects of peripheral DN‐9 in various pain models. Experimental Approach: Antinociceptive effects of DN‐9 were assessed in nociceptive, inflammatory, and neuropathic pain. Whole‐cell patch‐clamp and calcium imaging assays were used to evaluate the inhibitory effects of DN‐9 to calcium current and high‐K + ‐induced intracellular calcium ([Ca 2+ ]i ) on dorsal root ganglion (DRG) neurons respectively. Side effects of DN‐9 were evaluated in antinociceptive tolerance, abuse, gastrointestinal transit, and rotarod tests. Key Results: DN‐9, given subcutaneously, dose‐dependently produced antinociception via peripheral opioid receptors in different pain models without sex difference. In addition, DN‐9 exhibited more potent ability than morphine to inhibit calcium current and high‐K + ‐induced [Ca 2+ ]i in DRG neurons. Repeated treatment with DN‐9 produced equivalent antinociception for 8 days in multiple pain models, and DN‐9 also maintained potent analgesia in morphine‐tolerant mice. Furthermore, chronic DN‐9 administration had no apparent effect on the microglial activation of spinal cord. After subcutaneous injection, DN‐9 exhibited less abuse potential than morphine, as was gastroparesis and effects on motor coordination. Conclusions and Implications: DN‐9 produces potent analgesia with minimal side effects, which strengthen the candidacy of peripherally acting opioids with multifunctional agonistic properties to enter human studies to alleviate the current highly problematic misuse of classic opioids on a large scale.